2016
DOI: 10.1007/s13181-016-0552-x
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Concerns Due to Expanded Cannabis Use: Unintended Consequences of Legalization

Abstract: An "unintended consequence" of marijuana legalization is the impact on the pediatric population. From prenatal exposure to unintentional childhood exposures, through concerns of adolescence abuse and marijuana use for medicinal indications in children, marijuana exposure can affect pediatric patients at every stage in childhood. Regardless of the stage or reason of exposure, concerns exist about short-term and long-term consequences in a child's physical and mental health. The use of cannabidiol (CBD) may have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 73 publications
0
38
0
Order By: Relevance
“…The use of marijuana during pregnancy could have implications for foetal brain development . Marijuana is lipid soluble and able to cross the placenta and blood‐brain barrier to accumulate in foetal tissues including brain tissues .…”
Section: Introductionmentioning
confidence: 99%
“…The use of marijuana during pregnancy could have implications for foetal brain development . Marijuana is lipid soluble and able to cross the placenta and blood‐brain barrier to accumulate in foetal tissues including brain tissues .…”
Section: Introductionmentioning
confidence: 99%
“…skiing), driving, cycling and working. Although Shi found that the implementation of a state medical cannabis policy did not increase hospitalisations related to cannabis abuse or dependence significantly more than other states from 1997 to 2014, increases in acute cannabis intoxication have emerged as a concern in states that have legalised non‐medical cannabis . Whereas cannabis‐related paediatric (<10 years) poison centre calls increased by an average 19% per year in the USA from 2009 to 2015, Colorado saw a statistically higher 34% yearly increase .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in vitro studies also suggest possible immunosuppression, with lymphocyte apoptosis and reductions of interleukins 8 and 10 14 . There are no long term data regarding the use of cannabidiol; however, there are well documented adverse health effects of long term recreational cannabis use, including lower birth weight and detrimental impacts on cognitive function and attention for children exposed to cannabis in utero 4 , 42 . Chronic use of cannabis in adolescence was associated with poor academic performance, reduced high school graduation, increased incidence of other drug addiction and mental health disorders 4 , 42 .…”
Section: Safety Of Medicinal Cannabis Productsmentioning
confidence: 99%
“…There are no long term data regarding the use of cannabidiol; however, there are well documented adverse health effects of long term recreational cannabis use, including lower birth weight and detrimental impacts on cognitive function and attention for children exposed to cannabis in utero 4 , 42 . Chronic use of cannabis in adolescence was associated with poor academic performance, reduced high school graduation, increased incidence of other drug addiction and mental health disorders 4 , 42 . In US states where cannabis has been legalised, medical consultations for accidental paediatric cannabis exposure have increased by 30% in regional poison centre calls from 2005 and 2011, compared with a non‐significant increase of 1.5% per year in states where it has not been legalised 42 …”
Section: Safety Of Medicinal Cannabis Productsmentioning
confidence: 99%